2020
DOI: 10.1038/s41598-020-75491-x
|View full text |Cite
|
Sign up to set email alerts
|

Protection against SARS-CoV-2 by BCG vaccination is not supported by epidemiological analyses

Abstract: The Bacillus Calmette–Guerin (BCG) vaccine provides protection against tuberculosis (TB), and is thought to provide protection against non-TB infectious diseases. BCG vaccination has recently been proposed as a strategy to prevent infection with SARS-CoV-2 (CoV-2) to combat the COVID-19 outbreak, supported by its potential to boost innate immunity and initial epidemiological analyses which observed reduced severity of COVID-19 in countries with universal BCG vaccination policies. Seventeen clinical trials are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 23 publications
3
51
1
Order By: Relevance
“…Neither the implementation of rapid contract tracing with targeted isolation, widespread testing, nor regional lockdowns had been as readily deployed in many countries upon the analysis CRM in the present work 26 , 27 . Hensel et al found that for countries with high testing rates, BCG vaccination no longer correlated with incidence 28 . However, in countries with current BCG vaccination policies and higher rates of testing, BCG vaccination remained significantly associated with reduced rates of CRM 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither the implementation of rapid contract tracing with targeted isolation, widespread testing, nor regional lockdowns had been as readily deployed in many countries upon the analysis CRM in the present work 26 , 27 . Hensel et al found that for countries with high testing rates, BCG vaccination no longer correlated with incidence 28 . However, in countries with current BCG vaccination policies and higher rates of testing, BCG vaccination remained significantly associated with reduced rates of CRM 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Hensel et al found that for countries with high testing rates, BCG vaccination no longer correlated with incidence 28 . However, in countries with current BCG vaccination policies and higher rates of testing, BCG vaccination remained significantly associated with reduced rates of CRM 28 . For Israeli adults aged 35–41 with symptoms suggestive of COVID-19, no difference was found in incidence for those born during BCG vaccination programs or those born just after they ended.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, trained immunity induced by BCG vaccination protects from several viral infections ( 71 , 72 ). However, attempts to find an association between BCG vaccination status and COVID-19 severity have yielded inconclusive results ( 73 , 74 ).…”
Section: Trained Immunity and Covid-19mentioning
confidence: 99%
“…However, analysis of the available data has clearly highlighted that no definitive conclusions in this regard can be drawn, as the studies were not systematically corrected for confounding variables, such as cardiovascular death rates and smoking prevalence. When confounding variables were considered, no correlation between overall BCG vaccination policy and spread of SARS-CoV-2 and its associated mortality was found [ 62 ]. Further studies are ongoing.…”
Section: Previous Enhanced Activation Of the Innate Immune Systemmentioning
confidence: 99%